2018
DOI: 10.1002/jcb.27409
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor gamma coactivator‐1α/HSF1 axis effectively alleviates lipopolysaccharide‐induced acute lung injury via suppressing oxidative stress and inflammatory response

Abstract: Acute lung injury (ALI) interferes with lung function by causing pulmonary inflammation and oxidative stress. Suppressing intracellular reactive oxygen species (ROS) may block intracellular inflammation. Thus, the purpose of the current study was to investigate the roles of peroxisome proliferator-activated receptor gamma coactivator-1α (PGC1α)/HSF1 axis in an lipopolysaccharide (LPS)-induced ALI murine model and in RAW264.7 macrophages. In the LPS-administrated mouse model, the addition of PGC1α obviously ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Numerous studies have demonstrated the crucial role of the infiltration of inflammatory cells, which is caused by the inflammatory cytokines during the progress of LPSinduced ALI. Furthermore, some researchers also noted that the increased infiltration of inflammatory cells could enhance the synthesis and accumulation of ROS in lung tissues [2,4,6,12,13]. In our study, the levels of IL-6 and TNF-α in BAL were increased in the LPS-induced ALI, and treatment with the ferroptosis inhibitor Fer-1 decreased the levels of both IL-6 and TNF-α in BAL, indicating the relationship between ferroptosis and inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Numerous studies have demonstrated the crucial role of the infiltration of inflammatory cells, which is caused by the inflammatory cytokines during the progress of LPSinduced ALI. Furthermore, some researchers also noted that the increased infiltration of inflammatory cells could enhance the synthesis and accumulation of ROS in lung tissues [2,4,6,12,13]. In our study, the levels of IL-6 and TNF-α in BAL were increased in the LPS-induced ALI, and treatment with the ferroptosis inhibitor Fer-1 decreased the levels of both IL-6 and TNF-α in BAL, indicating the relationship between ferroptosis and inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, the use of LPS provides information about the effects of host inflammatory responses, which occur in bacterial infections [8,9]. Researchers have demonstrated that the intratracheal administration of LPS can induce the production of inflammatory mediators and reactive oxygen species (ROS), and worsen the lung tissue injury in an experimental animal model of ALI [10][11][12][13]. Therefore, the development of a novel treatment mode against LPS-induced ALI, which is based on inhibition of inflammation and oxidative stress, has attracted scientists' attention in both clinical and pre-clinical studies.…”
mentioning
confidence: 99%
“…Further, we also observed that puerarin-V significantly inhibited the expression of IL-6 and translation activity of NF-κB/IκB-α/IKKα/β. The probable reason for this effect is inhibition of the phosphorylation of downstream target proteins NF-κB/IκB-α/IKKα/β associated with PPAR-γ activation as PPAR-γ is considered as a master regulator in inhibiting recruitment of pro-inflammatory cytokines [37]. Moreover, as illustrated in the previous literature, puerarin-V has shown to suppress inflammatory mediators including IL-6, IL-2, iNOS, NF-κB/IKK-α and COX-2 expression [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest PGC1α signaling to be involved in the NO-to-H2O2 switch in EDD in diabetic coronary arteries and miR-21 regulates PGC1α signaling. PGC1α is reported to have a host of functions including; antioxidant effects [23], prevention of oxidative stress [54], reduction of the expression of antioxidant-associated genes [11], reversed the overexpression of Sod1, Sod2 and catalase induced by ROS [16], diminished iNos as well as its NO by-product [18], promote eNOS expression [14] and is involved in regulating Cav-1 promoters [34]. Importantly, the loss of PGC-1α in non-CAD coronary arterioles produced a diseased (CAD) phenotype characterized by a shift from NO-to H2O2mediated dilation [28].…”
Section: Discussionmentioning
confidence: 99%